ATTITUDE AND PURCHASE INTENTION TOWARDS TEMPE PRODUCERS JOINING THE PROTESTS A Study in Central Java - Kresno Agus Hendarto; Basu Swastha Dharmmesta; B. M Purwanto; Moira M. M Moeliono (EKUITAS (Jurnal Ekonomi dan Keuangan), 2016)
The theory of attribution has been widely used in marketing studies. However, this theory contains some limitations as well. Using the context of protests of tempe producers, this study aims at minimizing the limitations by integrating the attribution theory with collective action theories, prosocial theories, and expectancy-value theories in explaining and predicting the behavior of product consumers and individuals/groups that joined the protests. To answer the research objectives, this study proposed a model integrating the attribution of perceived motives of tempe producers joining the, empathy towards tempe producers, attitude towards tempe producers, and subsequent purchasing intention. The results indicate that the proposed model is supported by the data. This implies that the integration of the attribution theory with collective action theories, prosocial theories, and expectancy-value theories can minimize the limitations with regard to the criticism in neglecting motivation in attribution processes and confounding between attribution processes and attributional processes.